Distributed Collaborative Optimization of a Multi-Region Integrated Energy System Based on Edge Computing Unit - Wang, Mengxue; Zhao, Haoran; Tian, Hang; Wu, Qiuwei (Frontiers in Energy Research, 2022)
The coordinated optimization scheduling of integrated energy systems is vital in multi-energy complementarity and hierarchical utilization. However, centralized optimization is inferior to the distributed optimization of the large-scale multi-region integrated energy system (MRIES) in data processing capacity and information security. This paper proposes a distributed computing architecture based on edge computing unit (ECU), which takes the energy hub as the main body, and sets the partitioning principle and method of MRIES. The ECU can finally realize the whole-system collaborative optimization of MRIES, which contains electrical, natural gas, and district heating networks, through internal autonomous optimization and boundary information interaction with the cloud computing center. At the same time, an improved nested based on the consensus-alternating direction method of multipliers is proposed, which ensures the convergence of mixed-integer linear program and effectively improves the convergence speed. Combining the advantages of the model and algorithm provides theoretical and algorithmic support for the optimization research of MRIES.